Clinical features and prognosis of lung cancer in patients with connective tissue diseases: a retrospective cohort study - Li, Ningning; Gao, Liwei; Bai, Chunmei; Zhao, Lin; Shao, Yajuan (Frontiers in Oncology, 2023)
Background Studies have demonstrated a close association between connective tissue diseases (CTDs) and lung cancer (LC). Evidence supports that poor survival may be associated with the presence of CTDs in patients with LC. Methods This retrospective cohort study investigated 29 patients with LC with CTDs, and 116 patients with LC without CTDs were enrolled as case-matched control cohorts. Medical records, therapeutic efficacy of cancer, and outcomes were analyzed. Results The median duration from the diagnosis of CTDs to LC was 17 years. The Eastern Cooperative Oncology Group (ECOG) performance score for LC-CTD patients was worse than that for matched non-CTD LC patients. The median progression-free survival (mPFS) and overall survival (mOS) of first-line chemotherapy did not differ between patients with lung adenocarcinoma (AC) with and without CTDs. A significant difference was observed in mPFS [4 months vs. 17 months; hazard ratio (HR), 9.987; p = 0.004] and mOS (6 months vs. 35 months; HR, 26.009; p < 0.001) of first-line epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) treatment between patients with AC with and without CTDs. The presence of CTD, sex, ECOG performance status, and tumor-node-metastasis clinical stage were the independent prognostic factors in all patients with non–small cell LC (NSCLC). ECOG performance status was determined to be an independent prognostic factor in patients with LC-CTD. In patients with NSCLC with CTD (n = 26), sex (male) and worse ECOG score were the independent poor prognostic factors. Conclusions CTDs were associated with poor survival in patients with LC. The therapeutic efficacy of first-line EGFR-TKI therapy was significantly worse in patients with lung AC with CTDs than in those without CTDs. ECOG performance status was determined as an independent prognostic factor for patients with LC and CTDs.